Mapping protein interactions of sodium channel NaV1.7 using epitope‐tagged gene‐targeted mice. (15th January 2018) - Kanellopoulos, Alexandros H; Koenig, Jennifer; Huang, Honglei; Pyrski, Martina; Millet, Queensta; Lolignier, Stéphane; Morohashi, Toru; Gossage, Samuel J; Jay, Maude; Linley, John E; Baskozos, Georgios; Kessler, Benedikt M; et al.
Abstract: The voltage‐gated sodium channel NaV 1.7 plays a critical role in pain pathways. We generated an epitope‐tagged NaV 1.7 mouse that showed normal pain behaviours to identify channel‐interacting proteins. Analysis of NaV 1.7 complexes affinity‐purified under native conditions by mass spectrometry revealed 267 proteins associated with Nav1.7 in vivo . The sodium channel β3 (Scn3b), rather than the β1 subunit, complexes with Nav1.7, and we demonstrate an interaction between collapsing‐response mediator protein (Crmp2) and Nav1.7, through which the analgesic drug lacosamide regulates Nav1.7 current density. Novel NaV 1.7 protein interactors including membrane‐trafficking protein synaptotagmin‐2 (Syt2), L‐type amino acid transporter 1 (Lat1) and transmembrane P24‐trafficking protein 10 (Tmed10) together with Scn3b and Crmp2 were validated by co‐immunoprecipitation (Co‐IP) from sensory neuron extract. Nav1.7, known to regulate opioid receptor efficacy, interacts with the G protein‐regulated inducer of neurite outgrowth (Gprin1), an opioid receptor‐binding protein, demonstrating a physical and functional link between Nav1.7 and opioid signalling. Further information on physiological interactions provided with this normal epitope‐tagged mouse should provide useful insights into the many functions now associated with the NaV 1.7 channel. Synopsis: Numerous novel protein‐protein interactors of voltage‐gated sodium channel NaV 1.7 were identified using mouse genetics combined with proteomic approaches. An epitope‐tagged (TAP tag) NaV 1.7 knock‐in mouse line was generated to investigate protein‐protein interactions of NaV 1.7. The TAP tag was inserted at the C‐terminus of NaV 1.7. The TAP‐tagged NaV 1.7 knock‐in mice show a normal NaV 1.7 expression pattern and normal pain behaviour. NaV 1.7 complexes were isolated from neuronal tissues from TAP‐tagged NaV 1.7 mice using affinity purification. Two hundred and sixty‐seven protein interactors of NaV 1.7 were identified by mass spectrometry (LC‐MS/MS) analyses following affinity purification. Abstract : Combining mouse genetics and proteomics reveals various new interactors of a voltage‐gated channel with key roles in pain perception, including direct links to opoid signalling and potential targets for better pain treatment.